Inadequacy of the asymptotic approximation for the interlayer coupling in Fe/Ag/Fe and Fe/Au/Fe (001) trilayers - FERREIRA, MAURO (American Physical Society, 1999)
We discuss the basic assumptions underlying the stationary phase approximation to the interlayer exchange coupling between magnetic materials across nonmagnetic spacers. We show that, for temperatures and spacer thicknesses of interest, it cannot be applied to systems such as Fe/Ag/Fe and Fe/Au/Fe (001) trilayers. Such inadequacy results from particular confinement effects caused by the Fe layers in the Ag and Au extremal Fermi-surface ?neck? states. This is of special relevance to the interpretation of experimental data.
PUBLISHED
Keywords: Physics